2020
DOI: 10.1177/1533033820926593
|View full text |Cite|
|
Sign up to set email alerts
|

Gamma Radiation-Attenuated Toxoplasma gondii Provokes Apoptosis in Ehrlich Ascites Carcinoma-Bearing Mice Generating Long-Lasting Immunity

Abstract: Purpose: Pathological angiogenesis and apoptosis evasions are common hallmarks of cancer. A different approach to the antitumor effect of parasitic diseases caused by certain protozoans and helminthes had been adopted in recent years as they can affect many cancer characteristics. The present work is an attempt to assess the effect of gamma radiation-attenuated Toxoplasma gondii ME49 as an antiapoptotic and angiogenic regulator modifier on tumor growth aimed at improving cancer protective protocols. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
(85 reference statements)
2
16
0
Order By: Relevance
“…Due to the substantial proliferation of connective tissue, the oxygen supply is insufficient. When the tumor’s oxygen supply is insufficient to meet the needs of tumor cells, it is necessary to increase the oxygen supply through neovascularization or angiogenesis [ 44 ]. The highly dense blood vessels also increase the probability of tumor metastasis [ 45 ].…”
Section: Angiogenesismentioning
confidence: 99%
“…Due to the substantial proliferation of connective tissue, the oxygen supply is insufficient. When the tumor’s oxygen supply is insufficient to meet the needs of tumor cells, it is necessary to increase the oxygen supply through neovascularization or angiogenesis [ 44 ]. The highly dense blood vessels also increase the probability of tumor metastasis [ 45 ].…”
Section: Angiogenesismentioning
confidence: 99%
“… 34 To count the EAC cells before i.p injection, the bright line hemocytometer was used and trypan blue was added to count the viable cell under microscope. 35 The solid tumor was obtained by the intramuscular inoculation of 0.2 ml of 1 × 10 6 viable EAC cells in the right lower limb of each mouse. 36 Mice with a palpable solid tumor diameter (10 mm³) that was maintained within 7 to 10 days after inoculation were used for the study.…”
Section: Methodsmentioning
confidence: 99%
“…31 Our results showed that the average value of the activity of caspase 3 in the liver was 30. In addition, Hafez et al 32 found that EAC-inoculated mice had significantly lower levels of the apoptotic molecule caspase 3 than the control group. Tumour formation and proliferation are caused by the breakdown of apoptotic and angiogenic regulators.…”
Section: Ta B L E 1 3 Pearson's Correlationmentioning
confidence: 99%
“…Neovascularization increases the tumour's ability to grow, invasiveness and metastatic potential. 32 Most antineoplastic chemotherapies rely on the stimulation of intrinsic apoptotic mechanisms mediated by mitochondria to kill cancer cells.…”
Section: Ta B L E 1 3 Pearson's Correlationmentioning
confidence: 99%